Spousal Support and Work—Family Balance in Launching a Family Business - Gudmunson, Clinton G.; Danes, Sharon M.; Werbel, James D.; Loy, Johnben Teik-Cheok (Journal of family issues, 2009)
This study examines whether emotional spousal support contributes to business owners' perceived work—family balance while launching a family business. Hobfoll's Conservation of Resources theory of stress is applied to 109 family business owners and their spouses. Results from structural equation models support several hypotheses. First, reports of spousal support given are strongly related to reports of support received, suggesting genuine interpersonal transactions of support. Second, the effects of spousal support are confounded until a satisfaction-with-business-communication variable is introduced, revealing competing direct and indirect effects on work—family balance. Finally, business owner work hours have an additive negative effect on work—family balance, suggesting multiple means for maintaining work—family balance.